Thai Political Conflicts through the Perspectives of Vietnam’s Media - Rato, Montira (Journal of Mekong Societies, 2013)
This article attempts to analyze how Thai political conflicts were reported and represented in four Vietnamese online newspapers, Tuoi Tre, Vietnamnet Thanh Nien, and Nhan Dan, during the years 2004-2009. The political conflicts in Thailand receive tremendous attention from Vietnamese media, but they are carefully reported due to the fear that news and reports might affect Thai-Vietnamese relations. However, Vietnam’s media began to more openly express their views after the closure of Suvarnabhumi Airport and cancellation of the ASEAN Summit in Pattaya. This is because the two incidents had an impact on Vietnam’s economy, especially tourism. It is generally known that Vietnam’s media is closely regulated by the government and that it conforms to party lines. Thus, to some extent, the perspectives of Vietnam’s media can also reflect the Vietnamese government’s views of political situations in Thailand.